Novel Methods and Approaches for Safety Evaluation of Nanoparticle Formulations: A Focus Towards In Vitro Models and Adverse Outcome Pathways - Tirumala, Mounika Gayathri; Anchi, Pratibha; Raja, Susmitha; Rachamalla, Mahesh; Godugu, Chandraiah (Frontiers in Pharmacology, 2021)
Nanotoxicology is an emerging field employed in the assessment of unintentional hazardous effects produced by the nanoparticles (NPs) impacting human health and the environment. The nanotoxicity effects can be simple disturbances in the physiological functions of cells or organisms to death and may even be hazardous to the next generations through genotoxicity. Most of the reasons so far reported for toxicological effects of NPs are different sizes with high surface areas, shape, charge, and physicochemical properties, which upon interaction with the biological environments may influence their actual functioning and result in adverse outcomes. Thus, understanding the risk produced by these materials now is an important safety concern for the development of nanotechnology and nanomedicine. Since the time nanotoxicology has evolved, the methods employed have been majorly relied on in-vitro cell-based evaluations, while these simple methods may not predict the complexity involved in pre-clinical and clinical conditions concerning pharmacokinetics, organ toxicity, and toxicities evidenced through multiple cellular levels. There is a great concern on the safety profiles of different types of nanomaterials and nanoformulations used in drug delivery and biomedical applications. There are no proper regulatory guidelines for the safety evaluation of various innovative nanomedicine formulations. Though the in-vivo studies are greatly needed, the end parameters used for risk assessment are not predicting the possible toxic effects produced by various nanoformulations. On the other side, due to increased restrictions on animal usage and demand for the need for high throughput assays, there is a need for developing and exploring novel methods to evaluate nanoparticles safety concerns. The advancements in the field of molecular biology and the availability of various modern techniques may offer novel and innovative methods to evaluate the toxicological behavior of different nanoparticles by using single cells, cell population, and whole organisms. This review highlights the recent novel methods developed for the evaluation of the safety effects of NPs and tries to address the challenges involved in nanoparticle risk assessment. A special emphasis has been given on the important of exploring adverse outcome pathways (AOP) in nanotoxicology.